Decreased differentiation of erythroid cells exacerbates ineffective erythropoiesis in β-thalassemia - Libani, Ilaria V. (American Society of Hematology, 2008)
In β-thalassemia, the mechanism driving ineffective erythropoiesis (IE) is insufficiently understood. We analyzed mice affected by β-thalassemia and observed, unexpectedly, a relatively small increase in apoptosis of their erythroid cells compared with healthy mice. Therefore, we sought to determine whether IE could also be characterized by limited erythroid cell differentiation. In thalassemic mice, we observed that a greater than normal percentage of erythroid cells was in S-phase, exhibiting an erythroblast-like morphology. Thalassemic cells were associated with expression of cell cycle–promoting genes such as EpoR, Jak2, Cyclin-A, Cdk2, and Ki-67 and the antiapoptotic protein Bcl-X(L). The cells also differentiated less than normal erythroid ones in vitro. To investigate whether Jak2 could be responsible for the limited cell differentiation, we administered a Jak2 inhibitor, TG101209, to healthy and thalassemic mice. Exposure to TG101209 dramatically decreased the spleen size but also affected anemia. Although our data do not exclude a role for apoptosis in IE, we propose that expansion of the erythroid pool followed by limited cell differentiation exacerbates IE in thalassemia. In addition, these results suggest that use of Jak2 inhibitors has the potential to profoundly change the management of this disorder.